Wood capillarity and deacetylation during eucalyptus alkaline impregnation. Suphidity effects and comparison between transverse directions - Inalbon, Maria Cristina (2013)
The relative ion transport capacity of wood, i.e., the Effective Capillary Cross Sectional Area (ECCSA), is determined in this work based on the analogy with the relation between the electrical conductivities of wood and liquid medium. Wood is treated under different conditions and then the corresponding ECCSAA (effective capillarity under alkali) is estimated from the value obtained in an inert solution at room temperature (ECCSAInert). The difference between radial and tangential ECCSAA-values can be considered similar irrespectively of pH, time, temperature and the presence of sodium sulfide in the treatment liquor. The results show that the degree of removal of native acetyl groups from hardwood O-acetyl-glucuronoxylan is determinant of a physical characteristic, the ECCSAA. A kinetic expression for Eucalyptus wood deacetylation is validated and used to establish the relationship between the acetyl content and ECCSAA in both directions.